Rising Growth, Declining Investment : The Puzzle of the Philippines - Bocchi, Alessandro Magnoli (World Bank, Washington, DC, 2012)
The economy of the Philippines is open to trade and capital inflows, and has grown rapidly since 2002. Over the last 10 years, however, domestic investment, while stagnant in real terms, has shrunk as a share of GDP. In an open and growing economy, why the decline? Three reasons explain the puzzle. First, the public sector cannot afford expanding its investment at GDP growth rates. Second, the capital-intensive private sector does not find it convenient to raise investment at the economy's pace. Third, fast-growing businesses in the service sector do not need to rapidly increase investment to enjoy rising profits. Yet, the economy keeps growing. On the demand-side, massive labor migration results in remittances that fuel consumption-led-growth. On the supply-side, free from rent-capturing regulations, a few non-capital-intensive manufactures and services boost exports. The economic system is in equilibrium at a low level of capital stock, where all economic agents have no incentive to unilaterally increase investment and the first mover bears short-term costs. As a consequence, growth is slower and less inclusive than it could be. To make it speedier and more sustainable, and to reduce unemployment and poverty, the economy needs to move to a "high-capital-stock" equilibrium. This would be attainable through better-performing eco-zones, a competitive exchange rate, greater government revenues, and fewer elite-capturing regulations.